Anticoccidial effects of Galla rhois extract on Eimeria tenella-infected chicken - Lee, Hyun-A (Korean Association for Laboratory Animal Science, 2012)
Anticoccidial effects of Galla rhois (GR) extract were evaluated in chickens after oral infection with Eimeria tenella. This study was performed using 3-day-old chickens (n=30). The animals were divided into 3 groups as follows: GR 0.5%/infected (n=10), untreated/infected (n=10), and non-infected control (n=10). The chickens were fed a standard diet supplemented with or without GR for 1 week before infection with E. tenella (10,000 sporulated oocysts per chicken). The effects of GR on E. tenella infection were assessed by 2 parameters, number of fecal oocysts and body weight gain, and the results of the polymerase chain reaction (PCR). The GR-fed chickens produced significantly lower number of fecal oocysts (P<0.05) than the E. tenella-infected chickens who were fed the standard diet. In addition, GR-based diet improved the loss of body weight caused by E. tenella infection. Positive findings of PCR were identified by distinct bands in the samples of E. tenella-inoculated chickens. However, PCR analysis revealed no E. tenella oocysts in the feces of GR-fed chickens. Our data showed that GR extracts had remarkable anticoccidial activities against E. tenella. This finding might have implications for the development of novel anticoccidial drugs.